Grating-Assisted Surface Plasmon Resonance for Enhancement of Optical Harmonic Generation in Graphene - Zhao, Yan; Huo, Yanyan; Man, Baoyuan; Ning, Tingyin (Plasmonics (Norwell, Mass.), 2019)
We investigate nonlinear optical second- and third-harmonic generation from graphene covered on dielectric gratings. The nonlinear optical response in graphene is dramatically enhanced when surface plasmon of graphene is excited. Compared with graphene on a flat dielectric, the enhancement factor of second- and third-harmonic generation is up to 10 6 and 10 8 , respectively. We, in detail, studied the second- and third-harmonic generation intensity influenced by the angle of incidence, the Fermi level, and carrier mobility of graphene.